CLINICAL OUTCOME OF FRACTURES OF PROXIMAL HUMERUS TREATED BY CONSERVATIVE AND OPERATIVE PROCEDURES - DR.G.KISHORE ROY,; DR.K.R.V.KARTHIK, (International Journal of Pharma and Bio Sciences, 2016)
Proximal humerus fractures are on the rise due to osteoporosis by virtue of aging population besides rapid mode of transportation. Fractures of the proximal humerus have exponential increase after 40 years. For most undisplaced and minimally displaced fractures of the proximal humerus non-surgical management is preferred because fracture occurs in a metaphyseal bone and healing time is short. Displaced fractures in osteopenic bone, the techniques of internal fixation, with less disruptive soft tissue dissection, and minimal fixation with k wires.To study the clinical outcome of fractures of proximal humerus according to Neer’s classification treated by conservative (POP slab) and surgical procedures (k wiring, cancellous screws & plating). Depending upon the patient’s age, functional needs and radiological classification of fracture it was decided whether to treat the fracture conservatively and surgically. From this sample study, we conclude that the results of both conservative and surgical methods of treatment are satisfactory with appropriate patient selection and treatment procedure. That is :-Undisplaced fractures of the proximal humerus and undisplaced tuberosity fractures can be satisfactorily treated conservatively with J slab and gives good results.-Displaced greater tuberosity fractures can be preferably fixed internally with cancellous screws after open reduction.